INVESTMENT PORTFOLIO MANAGEMENT: PRINCIPLES, STRATEGIES, AND PERFORMANCE EVALUATION - Khaydarov, Khumoyun (International Conference on Business & Management, 2026)
Investment portfolio management is a core component of modern finance, aimed at achieving optimal returns while managing risk under conditions of uncertainty. This thesis examines the theoretical foundations and practical applications of investment portfolio management, with a particular focus on portfolio diversification, asset allocation strategies, and performance evaluation techniques. Drawing on classical and modern portfolio theories, the study analyzes how rational investors can construct efficient portfolios that balance risk and return. The research also highlights contemporary challenges in portfolio management, including market volatility, behavioral biases, and globalization of financial markets. The findings emphasize that a well-structured investment portfolio, supported by quantitative analysis and disciplined decision-making, plays a crucial role in long-term wealth creation.